1996
DOI: 10.1164/ajrccm.154.4.8887613
|View full text |Cite
|
Sign up to set email alerts
|

Elafin/elastase-specific inhibitor in bronchoalveolar lavage of normal subjects and farmer's lung.

Abstract: Secretory leukocyte proteinase inhibitor (SLPI) and alpha1-proteinase inhibitor (alpha1(PI)) cannot fully explain the total neutrophil elastase (NE) inhibitory capacity detected in bronchoalveolar lavage (BAL) fluid, suggesting the existence of other NE inhibitor(s). In the present study, we measured the concentrations of elafin, a newly described, low-molecular-weight serine proteinase inhibitor, SLPI, and alpha1(PI) in BAL fluids from eight healthy subjects, 13 asymptomatic farmers, seven farmers with active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 27 publications
0
41
0
Order By: Relevance
“…This therm oactinomycete is a causative agent of farmer's lung, a form of hypersensitivity pneumonitis (Corm ier and Schuyler, 1992). Interestingly, we already showed that, in contrast to SLPI, elafin levels are increased in bronchoalveolar lavage fluid of sub jects with this lung disease (Tremblay et al, 1996). This strongly suggests that alveolar macrophages, but not alveolar epithelial cells, are the cellular source of elafin in farm er's lung.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…This therm oactinomycete is a causative agent of farmer's lung, a form of hypersensitivity pneumonitis (Corm ier and Schuyler, 1992). Interestingly, we already showed that, in contrast to SLPI, elafin levels are increased in bronchoalveolar lavage fluid of sub jects with this lung disease (Tremblay et al, 1996). This strongly suggests that alveolar macrophages, but not alveolar epithelial cells, are the cellular source of elafin in farm er's lung.…”
Section: Discussionmentioning
confidence: 85%
“…Elafin and SLPI are two low molecular weight serine protease inhibitors that, together with a r antitrypsin, protect the fragile lung architecture from proteolytic, especially elastolytic, damage (Dijkman, 1995;Tremblay et al, 1996;M cElvaney and Crystal, 1997;Senior and Anthonisen, 1998). While CL}-antitrypsin is mainly synthesized by he patocytes (Perlmutter, 1993) and SLPI is locally produced by airway structural cells (Dijkm an, 1995), the cellular origin of elafin in the lung is yet unknown (Schalkwijk et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations